Effect of yeast-based selenium on blood progesterone, metabolites and milk yield in Achai dairy cows. Issue 1 (2nd January 2019) - Ullah, Hammad; Khan, Rifat Ullah; Mobashar, Muhammad; Ahmad, Shakoor; Sajid, Abdul; Khan, Naimat Ullah; Usman, Tahir; Khattak, Irfan; Khan, Hamayun
Abstract: The aim of present study was to find the influence of organic selenium (Se) on blood progesterone, metabolites and milk production in Achai dairy cows. A total of 45 cows were divided into three groups. One of these was control group. The 2nd and 3rd group were supplemented with yeast based Se at the rate of 0.3 and 0.4 mg/kg dry matter intake (DMI) respectively from the start of eighth month of pregnancy until parturition. Animals supplemented with organic Se at the rate of 0.3 and 0.4 mg/kg had significantly ( p  < .05) higher serum progesterone (P4) concentration (2.98 ng/mL) and milk production (3.94 L/day) respectively, exhibiting 24.8% higher milk production than the control group. Serum cortisol level was significantly lower (0.42 ug/dL) in animals supplemented with yeast based Se at the rate of 0.4 mg/kg DMI. Concentration of serum glucose, triglycerides and cholesterol did not differ among the groups. In conclusion, supplementation of yeast based Se improved the progesterone concentration, milk yield and reduced the stress in Achai dairy cattle. Highlights: Organic selenium (Se) improved milk yield in Achai cows Organic Se reduced stress in Achai cows Organic Se had no effect on blood metabolites